IMPROVING STUDENTS’ VOCABULARY USING TIKTOK AT XITH OF VOCATIONAL HIGH SCHOOL 4 BUNGO - Alawayiah, Mona (Universitas Muhammadiyah Muara Bungo, 2023)
This research discusses the problems of students at State Vocational High School 4 Bungo. This research aims to help students and teachers in English lessons, especially in enriching vocabulary, because from the observations that have been made by researchers, the vocabulary known by students is very low, which greatly affects students when they want to continue the lesson. Researchers chose Tik Tok as a learning medium at Vocational High School 4 Bungo because the TikTok application can be processed into an interesting and interactive learning medium for students.The research method used is classroom action research to improve the quality of learning and help empower teachers to solve learning problems at school. This research took place in two cycles of action. The first cycle occurred on Monday, July 17, 2023, and July 24, 2023; the second cycle occurred on Monday, July 31, 2023, and August 7, 2023. The subjects of this study were 11 students, consisting of 3 female students and 8 male students in class XI MM Vocational High School 4 Bungo.Based on the results of the pre-test conducted before treatment, only 2 students scored above the Minimum Completeness Criteria (KKM). After the researcher conducted cycle 1 and applied the treatment, then conducted a post-test, the results obtained were 6 students who scored above the Minimum Completeness Criteria (KKM). And in cycle 2, there were 9 people who scored above the KKM. So, the increase in student learning activities from pre-test, cycle I, to cycle II is 80%. From the results of the data analysis, it can be concluded that classroom action research using the Tik Tok application can enrich students' vocabulary.